THE EFFECT OF PRONE KNEELING STIMULATION ON OPTIMIZING THE CRAWN PHASE OF INFANTS IN BANGUN REJO VILLAGE, TANJUNG MORAWA DISTRICT, IN 2025 - Sianturi, Nova Christiana; Sinaga, Asnita; Damanik, Lisa Putri Utami; Simbolon, Rolasnih Lilista; Nendah Agretha, Sri Mulati; Simanullang, Ester (Journal of Psychology, 2026)
Stunting and motor development disorders are crucial global health issues for human resource quality, where Indonesia's national stunting prevalence still reached 21.5% in 2023. At the local level, a preliminary survey at Bangun Rejo Village indicated that 50% of mothers ignored the crawling phase due to a lack of literacy regarding the importance of gross motor stimulation. Background: The need for structured interventions such as prone kneeling stimulation is an important variable to be studied to accelerate the functional maturity of muscles and nerves during the golden period of infant growth. Purpose: This study aims to analyze the effect of prone kneeling stimulation on infants' crawling ability at Bangun Rejo Village, Tanjung Morawa District in 2025. Methods: The research design used a quasi-experiment with a one-group pretest-posttest design on a sample of 43 infants selected through total sampling technique. Data were collected through direct observation using the Crawling Guideline Australia guide sheet during the period of January–March 2025 and analyzed using the Chi-Square test at a 95% confidence level. Results: The research findings showed that the majority of respondents were aged 8–9 months (58.1%) and female (51.2%). Bivariate analysis revealed that infants given stimulation had a crawling success rate of 86.4%, while the group without stimulation only reached 38.1%. Statistical tests showed a p-value = 0.001, which means there is a significant relationship between prone kneeling stimulation and crawling ability. Conclusion: Prone kneeling intervention is proven effective in facilitating infants' gross motor development; therefore, it is suggested for health facilities to integrate this stimulation technique into routine educational programs for parents..